(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
Sergey V. Grigoryan, Academician of the National Academy of Sciences of the Republic of Armenia, Doctor of Geological and Mineral Sciences, Professor, the largest geologist-geochemist, turned 80 years old.